A method to improve the quality of 2.5 dimensional micro-and nano-structures produced by focused ion beam machining. (October 2017) - De Felicis, Daniele; Mughal, Muhammad Zeeshan; Bemporad, Edoardo
Graphical abstract: Highlights: Stream file generation to obtain accurate, scalable and geometric-sensitive milling routines. A novel scan strategy, sensitive to the pattern local geometry. High accuracy micro-and nano-scale patterns using FIB micro machining. Abstract: The present work deals with a new technique to produce complex micro- and nano-scale patterns with high accuracy by FIB micro machining. The proposed method is related to the production of stream file, which is optimized through a software interface. A unique sampling approach is used to optimize the conversion from a 3D meshed CAD object to the focused ion beam (FIB) digital to analogue converter (DAC). The method uses a novel scan strategy, sensitive to the pattern local geometry and size, to define the optimal ion beam path, dwell time and the scanning pitch. This not only allows to minimize the redeposition but also to obtain accurate and scalable milling routines. In order to show the applicability of the method, a hemisphere and a pyramid shape are milled and compared to the shapes obtained using the conventional techniques. Results show that the method is very effective in producing complex shapes while overcoming the detrimental effect of conventional raster/serpentine FIB strategies, such as redeposition. Lastly, a fish-net structure with a pitch of ∼200 nm as well as a series of truncated cones with sub-micrometrical details are realized to show the potential impact of this new method. Results show that a spatial resolution of less than 100 nm is achievable with the help of this method.